Barton Stone's Unorthodox Christology - MacKinzie, Gregory E. (Stone-Campbell journal, 2010)
For Barton W. Stone, agreement with the Bible's statements about Christ was the most that one could require of a believer's Christology. Any teaching beyond these statements, such as the doctrine of the Trinity, was at best an opinion and at worst a threat to the unity of the church. Stone desired to demonstrate the viability of unity among "Bible only" Christians, yet his literal-logical hermeneutic was at odds with the need for Christianity's essential confessions to have meaning beyond recitation of Bible words.